Cool Crosby - Sateren, Shelley Swanson; Melmon, Deborah (North Mankato, Minnesota Picture Window Books, a Capstone imprint, 2017)
Alfie Wolfe thinks his twin sister is the biggest pain in the world and they are constantly getting into fights, until he observes how patiently the German shepherd Crosby at the Hound Hotel behaves with his super annoying little "brother" puppy, Bruno
English stories
a gift from book africa
1 2 13 15
Keywords: Dogs -- Juvenile fiction; German shepherd dog -- Juvenile fiction